Valoración Ambiental del Bosque Siempreverde Montano Bajo de la Cordillera Occidental de los Andes (BsBnO4), Ubicada en los Cantones Pujilí – La Maná, 2021. - Tasinchano Nacevilla, Jennifer Alexandra (2021)
At this research an environmental assessment of Lower Montane Evergreen Forest of Anden Western Cordillera was made, located in Pujilí and La Maná cantons in Cotopaxi Province corresponding to altitude floor of 1400-2000 meters above sea level. In this place the current diagnosis of the forest was established, for this research shapes of texture and vegetation cover were used to determine current use of the soil at study area, where it was proceeded to formulate alternatives for environmental and economic conservation. The used methodology for this project development was based on the application of inductive, deductive and descriptive methods, which allowed to establish qualitative and quantitative values on current forest reality, based on survey technique applying no probabilistic method that allowed to get information from main actors who are owners of properties at study sector. The main results are based on Shannon index application, which is used to determine biodiversity in the forest, obtaining a value of 2.93 H, which allows to determine that at incidence area the biodiversity is low, this is due to agriculture and inappropriate practices on ecosystem resources, having 43% of total area that is being used for agricultural sector and only 21% of native forests of total territory with a high ecological value. It can be concluded that the main causes of the loss biodiversity and extinction of species are due to the agricultural frontier increase, since these production practices are frustrating and the environment is severely deteriorated to the pressure on the soil and resources, which is why life conditions have not improved at incidence area.